Proteínas da maquinaria de exocitose da insulina, formação do complexo SNARE e concentração intracelular de Ca2+ em ilhotas pancreáticas de ratos jovens submetidos à desnutrição proteica na vida intrauterina e pós desmame - Lopes, Bruna Vieira (2012)
We investigated the kinetics of glucose-induced insulin secretion and its relationship with some elements involved in exocytosis of insulin granules in pancreatic islets from rats subjected to protein restriction. Male Wistar rats were divided into two groups: control (C) and low-protein (LP) fed, respectively, with a diet containing 17% and 6% of protein, since intrauterine life up to 40 days of life. Glucose evoked insulin secretion in both groups, with basal (2.8 mmol/L) and stimulated (22.2 mmol/L) secretion significantly reduced in LP compared to C islets. LP group showed a decrease in first and second phases of glucosestimulated insulin secretion and a decrease in glucose oxidation and concentration of intracellular calcium. There was also an increase of the syntaxin 1A and VAMP-2 and a reduction of the syntaxin4 and synaptotagmin7 expressions. Other proteins analyzed (Munc18, SNAP-25, PKCα, PKA, CaMKII and SERCA3) and the association between syntaxin 4 - Munc18 were not different between groups as did to all mRNA analysed. Finally, the LP islets showed an increase of the SNARE complex, but no time-dependent change in the pattern of complex formation during challenge with glucose. Thus, the damage in the secretory response to glucose by LP islets could, at least partly, be explained by changes in glucose metabolism, Ca2+ handling, and SNARE complex formation and proteins involved. SNARE complex data could also indicates the importance of the stoichiometry of its proteins participating and its pattern of the formation for the functionality of the complex.